Different Types of Visual Perturbation Induced Different Demands and Patterns in Active Control: Implication for Future Sensorimotor Training - Ren, Muchen; Lin, Tangdi; Chien, Jung Hung (Frontiers in Physiology, 2022)
Background: Sensorimotor training using visual perturbations has been widely applied to astronauts for rapidly handling and adapting to unpredictable environments. However, these visual perturbations might not be strong enough to trigger long-term effects. Therefore, this study aimed to develop a novel sensorimotor training paradigm using pseudo-random visual perturbations and to determine the demands and the patterns of active control under different types of visual perturbations. Method: Thirty healthy young adults participated in this study. Four walking conditions were randomly assigned to these participants: 1) walking without optic flow (NoOptic), 2) walking with the optic flow (Optic), 3) walking under reduced visual capability (Vre), and 4) walking under perturbed optic flow (Vpe). The dependent variables were the step length variability, the step width variability, the 95% confidence interval ellipse area, the long axis of the ellipse, and the short axis of the ellipse. Results: The results indicated that 1) the step length variability and the ellipse area were greater in Vre compared to Optic (p < 0.001, p < 0.001). Moreover, the step width variability and ellipse area were greater in Vpe than Optic (p < 0.001, p = 0.002). Conclusions: The above-mentioned results demonstrated that 1) walking in both Vre and Vpe conditions required greater demands and different patterns in active controls compared to the Optic condition, suggesting both Vre and Vpe conditions could be applied for sensorimotor training; and 2) the Vre condition would be the first choice if there were no concerns in potential trips on the treadmill.